Behaviour of a new type of shear connector for steel-concrete composite construction. (2021) - Vijayakumar, R.; Pannirselvam, N.
Abstract: The objective of this study was to investigate the structural behaviour of a new type of shear connector developed known as the Embossed Steel Plate connector (ESP). The need for the development for a new type of shear connector was due to the advancement of composite structures which subsequently enhances the composite behaviour as the shear connectors plays an important role in predominating the bearing capacity of the composite structure as a whole. Therefore, this study attempted to explore the structural behaviour of the newly developed shear connector by conducting push out test in accordance with Eurocode 4. The test results were correlated with the conventional head stud shear connectors and the structural behaviour of ESP connector was evaluated from the load slip curves.